2016
DOI: 10.21432/t22k6r
|View full text |Cite
|
Sign up to set email alerts
|

Collective Digital Storytelling: An Activity-theoretical Analysis of Second Language Learning and Teaching | Les histoires numériques collectives : une analyse systémique de l’activité d’apprentissage-enseignement d’une langue seconde

Abstract: This paper describes the collective activity of a group of four students who created a digital story as a teaching resource that was to be used for teaching English as a foreign language. It uncovers and analyzes the actual processes underlining the activity as it unfolds from one stage to another. Four processes, viz., sociocognitive interactions, methodological processes, reflective processes and techno-semiopragmatic interactions were identified during the unfolding of the collective activity. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…They were satisfied with groupmates' collaborative efforts and contributions. While most of the digital storytelling studies I discussed in the literature review involved individual projects, the findings of the present study and other studies involving group projects (Albano & Iacono, 2019;Alcantud Diaz, 2016;Kalyaniwala-Thapliyal, 2016;Røkenes, 2016) suggest that collaborative digital storytelling projects can be positive experiences. Pre-service EFL teachers in Røkenes (2016), for example, found group work to be "helpful and efficient" (p. 322).…”
Section: Enjoyment Motivation and Collaborationsupporting
confidence: 41%
See 1 more Smart Citation
“…They were satisfied with groupmates' collaborative efforts and contributions. While most of the digital storytelling studies I discussed in the literature review involved individual projects, the findings of the present study and other studies involving group projects (Albano & Iacono, 2019;Alcantud Diaz, 2016;Kalyaniwala-Thapliyal, 2016;Røkenes, 2016) suggest that collaborative digital storytelling projects can be positive experiences. Pre-service EFL teachers in Røkenes (2016), for example, found group work to be "helpful and efficient" (p. 322).…”
Section: Enjoyment Motivation and Collaborationsupporting
confidence: 41%
“…Other digital storytelling studies have involved education majors from multiple disciplines (Heo, 2011;Hodge & Wright, 2010). The majority of digital storytelling studies that I have identified focus on undergraduate students (Kalyaniwala-Thapliyal, 2016;Kocaman-Karoglu, 2016), although some involve master's degree-level students (Dell Jones, 2018;Van Galen, 2017). Few studies appear to focus on doctoral students, particularly in the field of L2 education.…”
Section: Digital Storytelling In Teacher Education Researchmentioning
confidence: 99%
“…Commercial apps use decontextualized drills, thinly veiled by gamification strategies (e.g., rewards, badges) to keep learners in the "game" (see Lotherington et al, 2021, for discussion). The respondents' preferred digital activities and tools suggest a conservative bent in their digital participation and a lack of awareness or facility with innovative, agentive, and creative digital pedagogies that utilize digital tools for productive multimodal creation, such as digital storytelling (Anderson et al, 2018;Kalyaniwala-Thapliyal, 2016), cellphilms (MacEntee et al, 2016, collaborative game building, and gameplay (Reinders & Wattana, 2015;Scholz, 2017).…”
Section: What Digital Tools Are Fsl Tcs Using For Social Communicatio...mentioning
confidence: 99%